Potential mechanisms of coexistence in closely related forbs. Issue 12 (2nd May 2016) - Staples, Timothy L.; Dwyer, John M.; Loy, Xingwen; Mayfield, Margaret M.
Abstract : The stable coexistence of very similar species has perplexed ecologists for decades and has been central to the development of coexistence theory. According to modern coexistence theory, species can coexist stably (i.e. persist indefinitely with no long‐term density trends) as long as species' niche differences exceed competitive ability differences, even if these differences are very small. Recent studies have directly quantified niche and competitive ability differences in experimental communities at small spatial scales, but provide limited information about stable coexistence across spatial scales in heterogeneous natural communities. In this study, we use experimental and observational approaches to explore evidence for niche and competitive ability differences between two closely related, ecologically similar and widely coexisting annual forbs: Trachymene cyanopetala and T. ornata . We experimentally tested for stabilizing niche differences and competitive ability differences between these species by manipulating species' frequencies, under both well‐watered and water‐stressed conditions. We considered these experimental results in light of extensive field observations to explore evidence of niche segregation at a range of spatial scales. We found little evidence of intra‐specific stabilization or competitive ability differences in laboratory experiments while observational studies suggested niche segregation across pollinator assemblages and small‐scale microclimate heterogeneity. Though we did not quantify long‐term stabilization of coexisting populations of these species, results are consistent with expectations for stable coexistence of similar species via a spatial storage effect allowing niche differences to overcome even small (to absent) competitive ability differences.